Vol. 37 : Smart Grids 2015: September 28 - October 2, 2015, Tomsk, Russia; [proceedings]; MATEC Web of Conferences - Strizhak P. A. Pavel Alexandrovich; Gubin V. E. Vladimir Evgenievich; Zhdanova A. O. Alena Olegovna; Kuznetsov G. V. Geny Vladimirovich (Les Ulis, 2015)
Title screen